(untitled) (Journal of Environmental Bioremediation and Toxicology, 2024)
Primary modeling of microbial growth is essential for determining key parameters such as the maximum specific growth rate (μm), which are foundational for secondary modeling. Models such as the modified Gompertz, modified Logistic, modified Richards, Buchanan-3-phase, Baranyi-Roberts, modified Schnute, von Bertalanffy, and Morgan-Mercer-Flodin (MMF) models elucidate the impact of substrates on bacterial growth and biotransformation processes, which are vital for biotechnological applications such as wastewater treatment and bioremediation. In this study, the growth of a previously isolated phenol-degrading Pseudomonas sp. strain Neni-4 on phenol was modeled using the aforementioned primary models. Experimental data indicated that phenol concentrations ranging from 500 to 2500 mg/L were toxic, slowing bacterial growth and increasing lag periods from 5 to 7 hours. Among the primary models tested, the Huang model provided the best fit, evidenced by a high adjusted coefficient of determination, low RMSE, and AICc values, and favorable accuracy (AF) and bias factors (BF). The robustness of the Huang model highlights its suitability for modeling bacterial growth under toxic conditions, providing valuable insights for optimizing biotechnological processes that involve bacterial adaptation and growth under stress conditions. This model’s ability to accurately describe the growth kinetics under such challenging conditions makes it a reliable tool for further bioprocess optimization and environmental applications.